Taxonomic identity of the ghost ant, Tapinoma melanocephalum (Fabricius, 1793) (Formicidae: Dolichoderinae) - Guerrero, Roberto J. (Zootaxa, 2018)
This paper revises the taxonomy of Tapinoma melanocephalum (Fabricius, 1793) as follows: T. melanocephalum = Tapinoma luffae (Kuriam, 1955) syn. nov., = Tapinoma melanocephalum coronatum Forel, 1908 syn. nov., = Tapinoma melanocephalum malesianum Forel, 1913 syn. nov. A neotype of Tapinoma melanocephalum (Fabricius, 1793) is designed here. Lectotypes of Tapinoma melanocephalum coronatum Forel, 1908 and T. melanocephalum malesianum Forel, 1913 are designated. Formica wallacei is proposed as a replacement name for Formica familiaris (= T. melanocephalum senior synonym). The worker, queen and male are redescribed and diagnosed. The morphological variability of populations is discussed. All castes are included in full color images.